Implementation of Minimum Service Standards (MSS) at the Fire and Rescue Service of East Lombok Regency - Putri, Vivin Adyana; Sulaeman,; Ningsih, Septia (Mandalika Journal of Economics, Management, and Accounting, 2026)
This study aims to analyze the implementation of Minimum Service Standards (SPM) in the field of fire services at the Fire and Rescue Department of East Lombok Regency, identify supporting and inhibiting factors, and formulate improvement strategies to enhance the effectiveness and quality of public services. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results indicate that the implementation of SPM has been carried out in accordance with national policy as regulated in the Minister of Home Affairs Regulation (Permendagri) No. 18 of 2021, yet its execution remains suboptimal. The response time indicator generally meets the target of 7–15 minutes in areas near fire stations, but it is difficult to achieve in remote regions due to limited resources, equipment, and geographical constraints. Supporting factors include the strong commitment and professionalism of personnel, a structured coordination system, and the presence of community fire volunteers (Retkar). Meanwhile, obstacles include insufficient human resources, limited budget, inadequate infrastructure, and weak inter-agency coordination. The study recommends strengthening human resource capacity, establishing additional fire stations in each district, modernizing firefighting equipment, and developing a Master Plan for Fire and Rescue Management (RISKAP) to ensure a more responsive, professional, and nationally standardized emergency service system.